On Malefic Generosity, Repressive Tolerance and Post-Colonial Condescension: Considerations on White Adult Educators Racializing Adult Education Discourse - Stephen Brookfield (Adult Education Research Conference, 2005)
When White adult educators engage with the work of authors of color they often mean to treat these respectfully and to ensure these ideas are not marginalized by other Whites. However, in a racist and sexist society the racial group membership and socio-political location of White authors means they can easily end up promoting malefic generosity, repressive tolerance and post-colonial condescension.